CHAK-STATISTICAL ANALYSIS OF DENTAL EXAMINATIONS OF ACTIVITY DISORDERS IN THE LOWER JAW - Astanov O.M; Gaffarov S.A (Scholar Express Journal, 2021)
Various manifestations of CHPJB BFBS lead to changes in the activity of the SCC, nasopharynx, TJT muscles, auditory, visual and vestibular analyzers, cranial nerves, a serious set. For example, there are both opinions about stopping breathing during sleep, sleep pressure and spinal arteries, that these cases can shorten people's life expectancy to 15-20 years. At the same time, the etiology and pathogenesis of such a wide range of neurosomatic disorders in CHPJB BFBS remain controversial and uncertain
Keywords: CHPJB BFBS; SCC; nasopharynx; auditory